MULTITEMPORAL ANALYSIS OF MANGROVE LAND COVER CHANGES IN CILACAP COASTAL AREA USING RANDOM FOREST ALGORITHM (2019–2024) - Abdul Halim Siregar; Dodik Ridho Nurrochmat; Yudi Setiawan (RADJA PUBLIKA, 2026)
The mangrove area of ​​6,286.80 hectares, managed by KPH Banyumas Barat on the coast of Cilacap Regency, faces various anthropogenic pressures, including land conversion to fishponds, residential expansion, and port or fishing infrastructure. However, comprehensive studies on the temporal dynamics of mangrove land cover change in this area remain very limited, even though this information is essential for formulating effective conservation and management strategies. This study aims to examine the multitemporal dynamics of mangrove land cover change (2019–2024) in KPH Banyumas Barat, Cilacap Regency, using a machine learning approach that combines Sentinel-2 imagery, multispectral vegetation indices, and Random Forest classification on the Google Earth Engine platform. The results show a decline in mangrove cover of 533.6 ha over the 2019–2024 period. Two phases of change were identified: during 2019–2022, mangrove area showed an increasing trend of 46.4 ha, while during 2022–2024, mangrove area decreased by 580.1 ha due to both natural and anthropogenic processes, which may weaken the ecological functions of the area, reduce coastal protection against abrasion, and threaten the livelihoods of coastal fishing communities whose income depends directly on the productivity of the mangrove ecosystem.